Complement factor H protects mice from ischemic acute kidney injury but is not critical for controlling complement activation by glomerular IgM. Issue 5 (22nd February 2018) - Goetz, Lindsey; Laskowski, Jennifer; Renner, Brandon; Pickering, Matthew C.; Kulik, Liudmila; Klawitter, Jelena; Stites, Erik; Christians, Uwe; van der Vlag, Johan; Ravichandran, Kameswaran; Holers, V. Michael; Thurman, Joshua M.
Abstract: Natural IgM binds to glomerular epitopes in several progressive kidney diseases. Previous work has shown that IgM also binds within the glomerulus after ischemia/reperfusion (I/R) but does not fully activate the complement system. Factor H is a circulating complement regulatory protein, and congenital or acquired deficiency of factor H is a strong risk factor for several types of kidney disease. We hypothesized that factor H controls complement activation by IgM in the kidney after I/R, and that heterozygous factor H deficiency would permit IgM‐mediated complement activation and injury at this location. We found that mice with targeted heterozygous deletion of the gene for factor H developed more severe kidney injury after I/R than wild‐type controls, as expected, but that complement activation within the glomeruli remained well controlled. Furthermore, mice that are unable to generate soluble IgM were not protected from renal I/R, even in the setting of heterozygous factor H deficiency. These results demonstrate that factor H is important for limiting injury in the kidney after I/R, but it is not critical for controlling complement activation by immunoglobulin within the glomerulus in this setting. IgM binds to glomerular epitopes after I/R, but it is not a significant source of injury. Abstract : The complement cascade is activated in the kidney by two distinct mechanisms after ischemia/reperfusion. In the glomerulus, IgM binds to neoepitopes expressed on damaged cells and activates the classical pathway, but activation remains controlled at the level of C4. In the tubulointerstitium, decreased complement regulation permits activation of the alternative pathway. Soluble factor H controls this process, and more severe injury is seen in mice that are deficient in factor H.